Efeitos da crio e termoterapia contra o dano oxidativo induzido por distensão muscular em ratos - Carvalho, Nélson Rodrigues de (2012)
Skeletal muscle injuries are among the most frequent causes of functional impairment in muscle tissue, affecting the life quality and are primarily responsible for the loss of rhythm in the case of training athletes. The skeletal muscle lesion most frequent are contusion and strain injury. Thus, developing therapies that mitigate and might accelerate the rehabilitation process of injured tissue are of great importance. For this reason, therapeutic applications of physical agents are gaining prominence, especially in sports medicine for the treatment of skeletal muscle injury, but do not have the mechanism of action fully understood. This study was performed in order to examine whether the modulation of oxidative stress could be an important factor involved in the beneficial effect of cryo and thermoterapy on strain gastrocnemius muscle injury. Adult male Wistar rats were submitted to a strain injury and treated with the therapeutic agents in an isolated or combined form. Strain damages caused an increase in muscle and blood oxidative damage. We suggest that this oxidative damage is possible related to the impairment of the muscle cells structure since that we observed a significant positive correlation among the increase in plasma Creatine Kinase levels and in muscle and blood Dichlorofluorescein oxidized and Thiobarbituric acid reactive substance levels. The inflammatory response intensity seems to be also an important factor involved in the genesis of the oxidative damage in the initial moments that follows the muscle strain injury. The therapeutic cold seems to be more effective to prevent the damage induced by the strain injury possible due to its capacity to control the muscle cells structure impairment and also to modulate the inflammatory response intensity that follows a muscle strain injury.